Phong cách lãnh đạo toàn diện và sự đổi mới của nhóm: Vai trò của sự chia sẻ kiến thức trong nhóm và môi trường đổi mới trong tổ chức - Cao Văn Tâm; Nguyễn Đông Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Based on the input-process-output framework, the research suggests that inclusive leadership and within-team knowledge sharing are antecedents of team innovation. In addition, this research investigates the moderating role of innovative climate in organizations on the relationship between inclusive leadership and team innovation. With a sample surveyed from 392 leaders working at manufacturers processing and exporting agricultural and aquatic products, the results show that inclusive leadership has positive effects on within-team knowledge sharing and team innovation. Moreover, within-team knowledge sharing has a positive impact on team innovation and partially mediates the positive relationship between inclusive leadership and team innovation. Furthermore, innovative climate in organizations reinforces the positive effect of inclusive leadership on team innovation.